Acid base balance in quarter horses performing three barrel racing - Da Silva, Marco Augusto Giannoccaro; Gomide, Lina Maria Wehrle; Dias, Deborah Penteado Martins; Martins, Carla Braga; Albernaz, Raquel Mincarelli; Bernardi, Nara Saraiva; De Queiroz Neto, Antonio; De Lacerda Neto, José Corrêa (My University, 2013)
High intensity exercise, as performed during the Three Barrel Racing (3BR), demands great energy production in a very short period of time. This request is feasible via anaerobic metabolism activation. The anaerobic metabolism generates lactate and hydrogen prótons (H+) within the muscle fibers, which are spread through the circulation determining metabolic acidosis. The purpose of the present study was to evaluate possible changes in acid-base balance in Quarter Horses performing 3BR. Eight adult horses performing one 3BR were evaluated. Venous blood samples were obtained at rest before the race (baseline), and immediately after the end of 3BR. Lactate concentration, pH, bicarbonate ions concentration [HCO3 -] and partial pressure of carbon dioxide (PvCO2) were assessed. The obtained values were analyzed by t-Student test (P<0.05). Immediately after the race, blood lactate was markedly increased, and pH and [HCO3 -] decreased. No differences were detected on PvCO 2 values. The acid-base balance components analyzed in the present study indicate that Quarter Horses performing 3BR develop metabolic acidosis, even with the very short period of exercise. These findings highlight the significance of clinical follow-up after competition, aiming to evaluate the need of therapeutic intervention to correct the metabolic imbalance.
Equilíbrio ácido-base em equinos da raça quarto de milha participantes da prova dos três tambores
Keywords: Equine; Exercise; Lactate; Metabolic acidosis; Three Barrel Racing